2019
DOI: 10.1002/anie.201900788
|View full text |Cite
|
Sign up to set email alerts
|

A Singular System with Precise Dosing and Spatiotemporal Control of CRISPR‐Cas9

Abstract: Several genome engineering applications of CRISPR‐Cas9, an RNA‐guided DNA endonuclease, require precision control of Cas9 activity over dosage, timing, and targeted site in an organism. While some control of Cas9 activity over dose and time have been achieved using small molecules, and spatial control using light, no singular system with control over all the three attributes exists. Furthermore, the reported small‐molecule systems lack wide dynamic range, have background activity in the absence of the small‐mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 44 publications
(16 reference statements)
0
46
0
Order By: Relevance
“… 31 33 Therefore, we systematically generated fusions with various combinations by fusing the FKBP12 F36V tag to the N-terminal, C-terminal, or loop region of Cas9 and identified the N-terminal and loop fusion (NL-FKBP-Cas9) to yield complete degradation in the presence of dTAG while maintaining wild-type Cas9 activity in the absence of dTAG ( Figures S1–S5 ). 31 , 33 We initially tested the degradation potency of dTAG-13 and dTAG-47 that varied in linker length and the CRBN-binding ligand and found that dTAG-47 was more potent in inducing NL-FKBP-Cas9 degradation ( Figure S3 ). To further evaluate the potency of dTAG-47-induced Cas9 degradation, HEK293T cells transfected with NL-FKBP-Cas9 were treated with various concentrations of dTAG-47.…”
Section: Resultsmentioning
confidence: 99%
“… 31 33 Therefore, we systematically generated fusions with various combinations by fusing the FKBP12 F36V tag to the N-terminal, C-terminal, or loop region of Cas9 and identified the N-terminal and loop fusion (NL-FKBP-Cas9) to yield complete degradation in the presence of dTAG while maintaining wild-type Cas9 activity in the absence of dTAG ( Figures S1–S5 ). 31 , 33 We initially tested the degradation potency of dTAG-13 and dTAG-47 that varied in linker length and the CRBN-binding ligand and found that dTAG-47 was more potent in inducing NL-FKBP-Cas9 degradation ( Figure S3 ). To further evaluate the potency of dTAG-47-induced Cas9 degradation, HEK293T cells transfected with NL-FKBP-Cas9 were treated with various concentrations of dTAG-47.…”
Section: Resultsmentioning
confidence: 99%
“… 514 Additionally, the photouncaging of a Cas9 activator, trimethoprim, from 69b was used to control the activity of a CRISPR-Cas9 system in cell cultures. 515 …”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 99%
“…In addition, Choudhary et al. reported light‐activated dihydrofolate reductase (DHFR)‐fused Cas9 systems stabilized by uncaged trimethoprim (TMP) for photoregulation of gene transcription with low background and quick photoactivation [48] . The aromatic amino groups of trimethoprim were crucial for binding to fused Cas9 DHFR domains to prevent fusion Cas9 from proteasomal degradation.…”
Section: Photoregulation Of Mirna or Grna Functionsmentioning
confidence: 99%
“…In addition, Choudhary et al reported light-activated dihydrofolate reductase (DHFR)-fused Cas9 systems stabilized by uncaged trimethoprim (TMP) for photoregulation of gene transcription with low background and quick photoactivation. [48] The aromatic amino groups of trimethoprim were crucial for binding to fused Cas9 DHFR domains to prevent fusion Cas9 from proteasomal degradation. Upon 385 nm or 470 nm light irradiation, the bulky photolabile NPPOC or thiocoumarine groups modified at amino groups could remove from caged TMP derivatives to become active TMP, and further restore CRISPR-Cas9 genome editing.…”
Section: Caged Guide Rna For Crispr/cas9mentioning
confidence: 99%